Critical thinking, clinical reasoning, and clinical judgment : a practical approach - Alfaro-LeFevre, Rosalinda (St. Louis, Missouri : Saunders/Elsevier, 2013)
What's behind every healed patient? This text provides the tools needed to become a safe, competent nurse. Using a "how-to" approach, this book helps develop critical thinking, clinical reasoning, and test-taking skills in preparation for the NCLEX® Examination and, even more importantly, apply critical thinking and clinical reasoning to nursing practice. Critical thinking and clinical reasoning strategies come to life through the use of real-life scenarios and decision-making tools, all supported with evidence for why the strategies work. The author makes the concepts of critical thinking and clinical reasoning come alive, so student nurses can begin to think like a nurse and learn essential critical thinking and clinical judgment reasoning skills for nursing practice
What are critical thinking, clinical reasoning, and clinical judgment? -- How to develop critical thinking -- Clinical reasoning and clinical judgment -- Ethical reasoning, evidence-based practice, teaching others, teaching ourselves, and test-taking -- Practicing clinical reasoning skills : applying nursing process -- Developing interpersonal, teamwork, and self-management skills.
Includes index.
Keywords: NURSING